Management of Isolated Tubal Torsion (ALADIN) during Emergency Laparotomy in Infertile Women - Bella Aprilia; Raymond Surya; Bram Pradipta (Indonesian Socety of Obstetrics and Gynecology, 2022)
Introduction: Isolated tubal torsion (ITT) is rare cases with challenging to diagnose. We would like to report ITT and primary infertility patient which came with acute abdominal pain. Case: A 36 yo female came to Koja Hospital with acute abdominal pain without sign of infections. Ultrasound findings show cystic mass on bilateral adnexal sized 76x28x39 mm and 31x51x43 mm with minimal ascites. During laparotomy, proximal right fallopian tube was torsioned four times clockwise. There was hydrosalping founded on contralateral tube, while right and left ovaries and uterus were normal. We performed salpingectomy. Discussion: The clinical presentation of ITT is non-specific and it has become a challenge to physician to develop preoperative diagnosis. The spectrum of imaging findings may be wide range depending on adnexal pathology, degree of severity, and the duration of adnexal torsion. The recommendation of primary approach to tubal torsion is conservative management considering ALADIN (mALignAncy-Death tissue, INfertility). Conclusion: The diagnosis is rarely be made before operation, due to non-specific clinical symptoms and imaging findings. The considerations to perform conservative management are malignancy, death tissue/necrotic, and infertility.